PENGARUH KUALITAS PRODUK, KEMASAN DAN HARGA TERHADAPKEPUASAN DAN LOYALITAS PELANGGAN BERAS SEHAT S. ORGANIK PRODUKSI CV. KHANON GARDEN & COLLECTION DI KABUPATEN SLEMAN - Suroto Suroto; Budiarto Budiarto; Nanik Dara Senjawati (Jurnal Dinamika Sosial Ekonomi, 2017)
The purpose of this research were to analyze the influence direct and indirect effects of product quality, packaging and price on customer satisfaction and loyalty Beras Sehat S. Organik production CV. Khanon Garden & Collection in Sleman Regency. The method used in this study is a quantitative method with a survey approach with observation, questionnaires and interviews. The measured variable is product quality, packaging and price variable with satisfaction as intervening variable to customer's loyalty of Beras Sehat S. Organik. Method of data analysis using descriptive analysis, multiple linear regression analysis. t test and path analysis. Interpretation of analysis results using 95% confidence level. The results showed that there is a direct influence of price on customer satisfaction and indirect influence of price on customer loyalty than the direct influence of satisfaction on customer loyalty of Beras Sehat S. Organik. Keyword: Product quality, packaging, price, satisfaction, loyalty.